Temporal trend of tuberculosis in the population deprived of Liberty in the State of Tocantins (Research, Society and Development, 2021)
Objective: The objective of the study was to analyze the trend of tuberculosis in the people deprived of liberty in the state of Tocantins between 2010 and 2019. Methods: Study time series based on data from the Department of Informatics of the Unified Health System. Analysis of the time trend was performed using the joinpoint regression model. Results: The tuberculosis incidence coefficient in PDL was 40 times higher than in the general population. According to joinpoint analysis, this indicator increased by 29.3% between 2010 and 2019 in the male PDL (APC: 29.3; CI: 13.7 to 47.1) and was stable in the female PDL (APC: 4.6; CI: - 9.1 to 20.5), the black PDL had a significant increase in tuberculosis (79.4%) between 2016 and 2019. The pulmonary clinical tuberculosis form grew 36.3% over the total period (APC: 36.3; CI: 15.6 to 60.6). All risk behaviors were responsible for the significant growth of tuberculosis cases in the PDL in the evaluated period, with smokers 23.1% (APC: 23.1; CI: 2.6 to 47.7), alcoholics 23.7% (APC: 23.7; CI: 16.6 to 31.2) and users of illicit drugs 29.8% (APC: 29.8; CI: 6.9 to 57.6). Conclusion: Although the state of Tocantins has a tuberculosis rate below the national level, the disease is hyper endemic in PDL and of increasing magnitude. This epidemiological pattern reports the need for public policies focused on diagnosis and timely strategies for monitoring cases to interrupt transmission.